Suplementação com ácidos graxos poliinsaturados (ômega 3 - EPA e DHA) para o tratamento de pacientes com epilepsia refratária : revisão sistemática e metanálise - Vasconcelos, Vivian Sarmento de [UNIFESP] (2017)
Objectives: To assess the effectiveness and safety of omega-3 polyunsaturated fatty acids (PUFA) in the control of seizures in patients with refractory epilepsy. Methods: Cochrane systematic review. We searched the following eletronic databases, without language restrictions: Cochrane Epilepsy Group Specialised Register, CENTRAL, MEDLINE, EMBASE, SCOPUS, LILACS and clinical trials registers. We included all randomised and quasi-randomised studies using PUFAs (in association with convential treatment) versus conventional treatment or other treatments for patients of any age with drug-resistant epilepsy. The following outcomes were assessed: seizure freedom, seizure reduction, improvement in quality of life, adverse effects and changes in plasma lipid profile. Two independent review authors were involved in study selection, data extraction and quality assessment of the included trials. Results: The search retrieved 71 citations, 8 studies were selected for full-text reading and 3 studies fulfilled the selection criteria and were included in the review. Two placebo controlled trials involving adults were conducted in developed countries, while one placebo controlled trial involving children was conducted in a developing country (Egypt). The three studies recruited a total of 155 subjects (85 adults and 70 children); 78 (43 adults and 35 children) were randomised to PUFAs and 77 (42 adults and 35 children) to placebo. All participants were followed for up to 12 weeks. Seizure freedom was reported by only one study, with a high risk of bias, involving exclusively children. The relative risk (RR) for this outcome was significantly higher in the children receiving PUFA compared to the control group: RR 20.00, 95% confidence interval (CI) 2.84 to 140.99, 1 study, 70 children. Similarly, PUFA supplementation was associated with a significant difference in the proportion of children with at least 50% reduction in seizure frequency: RR 33.00 95% CI 4.77 to 228.15, 1 study with a high risk of bias, 70 children. However, this effect was not observed when the data from two studies with adults were pooled: RR 0.57, 95% CI 0.19 to 1.75, I² 0%, 2 studies, 78 participants, low-quality evidence. None of the studies assessed bleeding as a potential adverse effect. There were no significant differences between the PUFA and control groups in relation to gastrointestinal effects: RR 0.78, 95% CI 0.32 to 1.89, 2 studies, 85 participants, low-quality evidence. Supplementation with PUFA did not produce significant differences in mean frequency of seizures, quality of life or other side effects. Conclusions: In view of the limited number of studies and small sample sizes, there is not enough evidence to support the use of PUFA supplementation in patients with refractory epilepsy. More trials are needed to assess the benefits of PUFA supplementation in the treatment of drug resistant epilepsy.